POTENTIAL AND PROSPECTS OF HALAL TOURISM IN IMPROVING REGIONAL ECONOMY (CASE STUDY: CILETUH GEOPARK, SUKABUMI-WEST JAVA) - Diza Izet Islamy; Malida NurAnnisa; Iasha Nabila Harahap (STIESA Press, 2020)
Sharia tourism is an activity that is supported by various facilities and services provided by the community, business people, government, and regional governments that meet the Sharia requirements. Where in the research this article focuses on the problem formula: (1) how the prospect of halal tourism in improving the regional economy in Sukabumi. This research was conducted using descriptive methods and qualitative approaches, data collection techniques conducted were observation, interviews, literature studies and document studies. The validity of the data is done by using data triangulation techniques, namely by checking the data that has been obtained through several other data sources. The informants in this study consisted of the local community, PAPSI officials (Paguyuban Alam Pakidulan Sukabumi) as a local institution that had attention and focus on Ciletuh Geopark management activities, as well as informants from local government elements. The results of the study are: (1) the potential and prospects of this halal tourism carried out that there are several tourist areas that are run by the community or Community Based Tourism (CBT) which has 5 aspects. The five aspects that run in the Ciletuh Port of Batu Geopark Area include economic, social, cultural, religious, political. Participation of local communities in the development and development of the Sharia tourism village is essential to build independence and maintain the continuity of the Sharia tourism village activities. Therefore, the local community should not be seen as an object of the development of the Sharia tourism village as Raharjana (2012) stated that the community should play an active role as the subject of development activities, as well as for the development of the Sharia tourism village.